Musculoskeletal disorders in university professors who telework due to COVID-19 pandemic - Cristancho, Angy Natalia; Almario Barrera, Andrea; Castellanos-Domínguez, Yeny (Universidad y Salud, 2022)
Introduction: Teaching virtually can cause symptoms related to muscle pain due to bad postures when working with computers. Objective: To determine the presence of musculoskeletal disorders in university professors who telework during the COVID-19 pandemic. Materials and methods: Analytical cross-sectional study in professors from health programs at a northeastern Colombian university. The validated Spanish version of the Nordic Kuorinka questionnaire was used (Cronbach’s alpha 0.8-0.9). Using non-probabilistic sampling and an instrument applied virtually, 68 professors were included in the study. The dependent variable was presence of musculoskeletal disorder, whereas the independent ones were the sociodemographic conditions related to telework. The Fisher or were used for qualitative variables. Comparison of means were carried out through Student’s t test. p<0.05 values were interpreted as statistical association. Results: 67.7% of participants reported musculoskeletal disorder in at least one anatomical site, being the neck the one mostly affected. Female gender and seniority in teaching practice showed an association with the disorder (p<0.05). Conclusion: Working conditions triggered by teleworking during the pandemic are associated with the presence of musculoskeletal disorders in professors.